Fan worms (Annelida: Sabellidae) from Indonesia collected by the Snellius II Expedition (1984) with descriptions of three new species and tube microstructure - María Ana Tovar-Hernández; Harry A. ten Hove; Olev Vinn; Michał Zatoń; Jesús Angel de León-González; María Elena García-Garza (PeerJ, 2020)
The Indonesian archipelago is one of the most diverse regions in the marine World. Many contributions on polychaete worms have been published since the Dutch Siboga Expedition to the Indonesian archipelago at the end of the 19th century. In this study, we examined specimens of Sabellidae Latreille, 1825 collected during the Snellius II Expedition (1984) to Indonesia, carried out by the Dutch Research Vessel (RV) “Tyro” and the Indonesian RV “Samudera”. The results include reports of Acromegalomma acrophthalmos, A. interruptum, A. sp., Bispira manicata, B. porifera, B. secusoluta, Branchiomma boholense, Notaulax pyrrohogaster, N. tenuitorques, N. sp. 3, Parasabella crassichaetae, Perkinsiana anodina, and Sabellastarte spectabilis. In addition, three new species are described: Acromegalomma sumbense sp. nov., Claviramus olivager sp. nov., and Notaulax montiporicola sp. nov., the latter in living coral (Montipora nodosa). Further, Sabella (Potamilla) polyophthalmos Grube is transferred to Pseudopotamilla. Additional histological accounts of B. porifera and tube microstructure of A. acrophthalmos, B. porifera, P. anodina, Pseudopotamilla polyophthalmos and Sabellastarte spectabilis are also included.